Gender Score Development in the Berlin Aging Study II : A Retrospective Approach - Ahmad Tauseef Nauman; Hassan Behlouli; Nicholas Alexander; Friederike Kendel; Johanna Drewelies; Konstantinos Mantantzis; Nora Berger; Gert G. Wagner; Denis Gerstorf; Ilja Demuth; Louise Pilote; Vera Regitz-Zagrosek (Biology of Sex Differences, 2021)
In addition to biological sex, gender, defined as the sociocultural dimension of being a woman or a man, plays a central role in health. However, there are so far few approaches to quantify gender in a retrospective manner in existing study datasets. We therefore aimed to develop a methodology that can be retrospectively applied to assess gender in existing cohorts. We used baseline data from the Berlin Aging Study II (BASE-II), obtained in 2009–2014 from 1869 participants aged 60 years and older. We identified 13 gender-related variables and used them to construct a gender score by using primary component and logistic regression analyses. Of these, nine variables contributed to a gender score: chronic stress, marital status, risk-taking behaviour, personality attributes: agreeableness, neuroticism, extraversion, loneliness, conscientiousness, and level of education. Females and males differed significantly in the distribution of the gender score, but a significant overlap was also found. Thus, we were able to develop a gender score in a retrospective manner from already collected data that characterized participants in addition to biological sex. This approach will allow researchers to introduce the notion of gender retrospectively into a large number of studies.
Keywords: 330; Gender; Sex; Aging; Berlin Aging Study II; Base-II; Gender score